Sigmoid colon perforation in a SARS-CoV-2 positive neonate: a uniqueness report and a brief review - Zahra Jamali; Reza Sinaei; Elahe Raeisi Estabragh; Ahmad Ahangaran (BMC, 2022)
Abstract Background Despite the relative prevalence of small bowel and proximal colon perforation in the neonatal period, recto-sigmoid perforation is extremely rare. Full-term neonates experience intestinal perforation less frequently than premature infants. Here we report a neonate with sigmoid perforation and simultaneous Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. Case presentation A 2550 g female neonate born at 38-weeks' gestation from a coronavirus disease-2019 (COVID-19) infected mother by cesarean section. Despite a good Apgar score in the first and fifth minutes, she was admitted to the neonatal intensive care unit with grunting and mild respiratory distress. She underwent antibiotics and oxygen by head box resulting in an Oxygen Saturation rate of 94%. The patients' respiratory distress decreased during the second day, resulting once breastfeeding without tolerance. While she passed meconium in the first 2 days, she developed abdominal distention on day 3. The nasopharyngeal SARS-CoV-2 real-time polymerase chain reaction (RT-PCR) was performed with positive results. Surgical consultation was requested and a thoraco-abdominal X-Ray was performed at this stage, which suspected to be a gastrointestinal perforation. Due to clinical deterioration and persistent abdominal distention, a contrast study was performed with water-soluble contrast, which confirmed intestinal perforation. However, the surgical exploration revealed perforation of the sigmoid colon at the posterior segment. The patient underwent antibiotic therapy, abdominal lavage, and colostomy, immediately. She was discharged in good condition approximately 14-days later. Conclusion To our knowledge, this is the first report of sigmoid colon perforation in a term neonate following COVID-19.